Inside installations : preservation and presentation of Installation Art. - Baumgart, Ulrike; Bek, Reinhard; te Brake-Baldock, Karen; Gordon, Craig; Grün, Maike; Heydenreich, Gunnar; Huys, Frederika; Kallinen, Sami; Lang, Ulrich; Laurenson, Pip; Scholte, Tatja; Wijers, Gaby; et al. (Amsterdam : ICN (Instituut Collectie Nederland) Amsterdam, 2007)
Aballi, Ignasi ; Barrio, Artur ; Bednarski, Krzysztof M. ; Collins, Phil ; Cruz, Angela de la ; Dean, Tacita ; Eliasson, Olafur ; van Elk, Ger ; Garaicoa, Carlos ; Grimonprez, Johan ; Hirschhorn, Thomas ; Holzer, Jenny ; Huyghe, Pierre ; Kinoshita, Suchan ; Kosuth, Joseph ; Lynn, Greg ; Marcaccio, Fabian ; Metzger, Gustav ; Nauman, Bruce ; Oppenheim, Dennis ; Paik, Nam June ; Panamarenko ; Parreno, Philippe ; Pérez, Javier ; Plessi, Fabrizio ; Rosenbach, Ulrike ; Sehgal, Tino ; Shaw, Jeffrey ; Sinclair, Ross ; Spinhoven, Bill ; van Tijen, Tjebbe ; Tuerlinckx, Joëlle ; Valldosera, Eulàlia ; West, Franz ; Zorio, Gilberto
boek